Analysis of aprepitant for prevention of chemotherapy-induced nausea and vomiting with moderately and highly emetogenic chemotherapy. (October 2013) - Molassiotis, Alex; Nguyen, Allison Martin; Rittenberg, Cynthia N; Makalinao, Alex; Carides, Alexandra
Aim: This study aimed to determine how aprepitant affects the impact of chemotherapy-induced nausea and vomiting (CINV) on daily activities during highly emetogenic chemotherapy (HEC) or moderately emetogenic chemotherapy (MEC).Patients & methods: Patients received aprepitant plus standard antiemetic therapy (ondansetron plus dexamethasone) or standard antiemetic therapy alone. Data were analyzed from pooled data of two Phase III randomized, double-blind HEC trials and one MEC trial. Patients completed the Functional Living Index–Emesis questionnaire.Results: A significantly greater percentage of patients receiving aprepitant reported no or minimal CINV impact on daily life (overall total Functional Living Index–Emesis score >6) compared with those receiving standard therapy alone (HEC: 74.4 vs 63.9%, respectively; p < 0.01; MEC: 73.4 vs 66.3%; p < 0.05). In HEC, favorable responses to aprepitant treatment persisted in nausea (70.2 vs 60.9%) and vomiting domains (84.6 vs 68.7%; both p < 0.01). Similar results were seen in MEC.Conclusion: Addition of aprepitant reduced CINV impact on daily life compared with standard antiemetic therapy.